Nursing assessment of people with bone metastases - Flores Hernández , Sarahi; Moctezuma Santillan , Areli; San Juan Antonio , Patricia; Oria Saavedra, C. Michel; Espinosa Aguilar , C. Anibal; López Pérez , Elisa (Salud Integral y Comunitaria, 2026)
Introduction:Bone metastasis is one of the most frequent complications in patients with advanced cancer, causing severe pain, functional limitation, and emotional distress. Nursing assessment is essential to identify needs and design individualized care that promotes patient well-being and quality of life.Objective:To present a nursing clinical case focused on the comprehensive assessment of a person with bone metastasis, applying the nursing process based on functional health patterns.Methods:A clinical case study was conducted on an adult female patient diagnosed with bone metastasis secondary to breast cancer. Data were collected through interviews, direct observation, and review of the clinical record. The assessment was carried out using Virginia Henderson’s model of the 14 fundamental needs, considering physical, psychological, and social dimensions.Results:The assessment identified priority problems related to cancer pain, reduced mobility, sleep disturbance, and ineffective coping. Nursing diagnoses and interventions were formulated focusing on pain control, emotional support, and self-care promotion. The implemented care plan improved comfort and patient participation in her treatment.Conclusions:This case demonstrates that comprehensive and systematic nursing assessment guides clinical decision-making and strengthens the autonomous role of nurses in managing patients with bone metastasis.